Molecular characterization of Gla-rich protein (GRP) gene expression and function - Fazenda, Cindy Vitória (2017)
Gla-rich protein (GRP) is a vitamin K-dependent protein related to bone and cartilage recently described. This protein is characterized by a large number of Gla (γ-carboxyglutamic acid) residues being the protein with the highest Gla content of any known protein. It was found in a widely variety of tissues but highest levels was found in skeletal and cartilaginous tissues. This small secreted protein was also expressed and accumulated in soft tissues and it was clearly associated with calcification pathologies in the same tissues. Although the biological importance of GRP remains to be elucidated, it was suggested a physiological role in cartilage development and calcification process during vertebrate skeleton formation. Using zebrafish, an accepted model to study skeletal development, we have described two grp paralog genes, grp1 and grp2, which exhibited distinct patterns of expression, suggesting different regulatory pathways for each gene. Gene synteny analysis showed that grp2 gene is more closely related to tetrapod grp, although grp1 gene was proposed to be the vertebrate ortholog by sequence comparison. In addition, we identified a functional promoter of grp2 gene and using a functional approach we confirmed the involvement of transcription factors from Sox family (Sox9b and Sox10) in the regulation of grp2 expression. In an effort to provide more information about the function of grp isoforms, we generated two zebrafish transgenic lines capable to overexpress conditionally grp genes and possible roles in the skeleton development were studied. To better understand GRP function a mammalian system was used and the analysis of knockout mice showed that GRP is involved in chondrocyte maturation and the absence of GRP is associated to proteoglycans loss in calcified articular cartilage. In addition, we detected differences in chondrogenesis markers in articular chondrocyte primary culture. Overall, our data suggest a main role for GRP on chondrocyte differentiation.